2018
DOI: 10.1161/cir.0000000000000580
|View full text |Cite|
|
Sign up to set email alerts
|

Atherosclerotic Cardiovascular Disease in South Asians in the United States: Epidemiology, Risk Factors, and Treatments: A Scientific Statement From the American Heart Association

Abstract: South Asians (from Bangladesh, Bhutan, India, the Maldives, Nepal, Pakistan, and Sri Lanka) make up one quarter of the world's population and are one of the fastest-growing ethnic groups in the United States. Although native South Asians share genetic and cultural risk factors with South Asians abroad, South Asians in the United States can differ in socioeconomic status, education, healthcare behaviors, attitudes, and health insurance, which can affect their risk and the treatment and outcomes of atherosclerot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
273
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 377 publications
(303 citation statements)
references
References 284 publications
6
273
1
1
Order By: Relevance
“…For example, we need to determine appropriate goals for waist circumference, BMI, and blood glucose levels to help reduce the burden of cardiometabolic diseases in this population [17; see also online suppl. material for additional references].…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, we need to determine appropriate goals for waist circumference, BMI, and blood glucose levels to help reduce the burden of cardiometabolic diseases in this population [17; see also online suppl. material for additional references].…”
Section: Future Directionsmentioning
confidence: 99%
“…However, in developing countries, this emerging public health issue is often overlooked [17]. South Asians are comparatively at an elevated risk for developing cardio-metabolic and other chronic diseases [18], which makes them more susceptible to multimorbidity. The Nepal STEPS survey, 2013 reported that 99.6% of the Nepali adults had at least one (of the eight known risk factors for chronic diseases) [19].…”
Section: Introductionmentioning
confidence: 99%
“…1 South Asia including Pakistan has the highest prevalence of CAD, ranging from more than 50% to 300% than the rest of the world. 2 In Pakistan, nearly 30% females of age >45 years are…”
Section: Introductionmentioning
confidence: 99%